Effects of institution, legal tradition and political factors on financial development - Voghouei, Hatra (2010)
This study deals with the effect of economic institutions, legal tradition and political factors on variation of financial development over 27 years where these determinants are themselves endogenous and determine by political factors. First, by considering the theory of “economic institution” proposed by Acemoglu et al (2004) this study indicates that two groups of political power (de jure political power or political institution and de facto political power or distribution of resource) determine the economic institutions which are important in variations of financial development. Second, by referring to the theory of “dynamic legal tradition” proposed by Beck et al (2001), it suggests that political factors in countries with different legal adaptability affect legal environments which are important in promoting the financial system. Third, it presents that the political factors directly and indirectly through other determinants of financial development could explain the variation of financial development over the years. By using the dynamic panel data of 60 countries during 1980-2006, the empirical results showed that de jure political power has more significant effect on financial development than de facto political power. These outcomes have important policy implications. The emphasis on strengthening de jure political factor through effective mechanism of checks and balance, promoting political competition and free stream of information, will help to put the economic institution in power that promote the development of financial system. The results support the idea that political power could change the legal environments which are important in development of financial systems. It showed that the political factors that promote shareholder rights and investor protection respectively could promote financial system more than the other factors. The results also showed that the effect of political changes on financial development in common law countries is more than this effect in German law countries. Finally, the results clarified that the development in financial system positively responds to variation of political variables. It showed that when the direct effect of political factors is considered the political stability has more effect on financial development than the other factors. Moreover, when the direct effect alongside the indirect effects through other determinants are considered, political stability has more impact in development of banking sector though, the effect of political competition on development of stock market is more than the others. Thus, different aspects of political factors which have positive effect on financial development could be used as policymakers’ tools in order to achieve more financial development and hence economic growth.